Effect of Thermally Activated Alum Sludge Ash and Nanoclay on the Mechanical Properties and Microstructure of Kenaf Fiber Reinforced Mortars - Ahmad, R.; Hamid, R.; A. Osman, S. (International Journal of Engineering and Technology, 2019)
This paper investigates the effect of thermally activated alum sludge ash (AASA) and nanoclay (NC) inclusion at various proportions on the mechanical properties and microstructure of kenaf fiber (KF) blended cementitious composites (KFRBCC). The first objective is to establish a blended cementitious (BC) composite with high mechanical strength. The BC materials used in this investigation comprises of various proportions of ordinary Portland cement (OPC), AASA and NC. Next, the influence of AASA and NC proportions on the properties of KFRBCC such as density and compressive, split tensile and flexural strengths, and microstructure are studied. The results show that the inclusion of AASA and NC improve the mechanical properties of the cementitious composite compared to all OPC mortar with or without KF. The enhancement in compressive strength is 50%, whereas the enhancement in split tensile and flexural strengths are 5.4% and 15%, respectively at optimum content of AASA and NC of 50 wt. % and 1 wt. %, respectively. The results also reveal that the microstructure of the composites is denser due to filler effect where the uniformly dispersed AASA and NC nano-particles had filled the voids/pores in the matrix compared to control specimens. AASA is proved to be benificial as one of cementitious replacement materials and its applicability as cement replacement in concrete should be explored further.Â Â